(In)dependence and addictions: Governmentality across public and private treatment discourses - Iacobucci, Alaina C. (Theoretical criminology, 2018)
In light of the current spike in opioid addiction in upper middle-class white populations, we examine addiction treatment discourses on the webpages of public methadone clinics and private rehabilitation facilities through a critical theoretical lens. While both discourses exercise social control over opioid-addicted clients by regulating their everyday practices, we find classed differences in these discourses when they are aimed at differently socially located populations. Private treatment discourses trust clients to be led to a state of self-governance through a holistic transformation of ‘mind, body, and spirit', while public clinics' websites frame patients as unruly bodies that must be chemically rendered docile through medication before they can return to everyday life.